The linguistic picture of St. Mary in John Henry Newman’s „Parochial and Plain Sermons” - Kuczok , Marcin (Studia Europaea Gnesnensia, 2018)
The aim of the paper is to analyze the linguistic picture of St Mary in John Henry Newman’s „Parochial and Plain Sermons” (1834-1843), published in the Anglican period of his life. The study focuses on identifying such elements of the linguistic picture of St. Mary as her titles and names, events from her life, various roles, attributes, and traits of personality depicted in Newman’s sermons.